Atomic-scale grain boundary engineering to overcome hot-cracking in additively-manufactured superalloys. (15th September 2019) - Kontis, Paraskevas; Chauvet, Edouard; Peng, Zirong; He, Junyang; da Silva, Alisson Kwiatkowski; Raabe, Dierk; Tassin, Catherine; Blandin, Jean-Jacques; Abed, Stéphane; Dendievel, Rémy; Gault, Baptiste; Martin, Guilhem
Abstract: There are still debates regarding the mechanisms that lead to hot cracking in parts build by additive manufacturing (AM) of non-weldable nickel-based superalloys. This lack of in-depth understanding of the root causes of hot cracking is an impediment to designing engineering parts for safety-critical applications. Here, we deploy a near-atomic-scale approach to investigate the details of the compositional decoration of grain boundaries in the coarse-grained, columnar microstructure in parts built from a non-weldable nickel-based superalloy by selective electron-beam melting. The progressive enrichment in Cr, Mo and B at grain boundaries over the course of the AM-typical successive solidification and remelting events, accompanied by solid-state diffusion, causes grain boundary segregation induced liquation. This observation is consistent with thermodynamic calculations. We demonstrate that by adjusting build parameters to obtain a fine-grained equiaxed or a columnar microstructure with grain width smaller than 100 μm enables to avoid cracking, despite strong grain boundary segregation. We find that the spread of critical solutes to a higher total interfacial area, combined with lower thermal stresses, helps to suppress interfacial liquation. Graphical abstract: Image 1